Experimental Study on Enhancement of Single-Basin Solar Still Using Dye Solutions - Kadhim H. S. AL-Zaedy (Engineering and Technology Journal, 2012)
An enhancement of single slope solar still using different dye solutions was studied experimentally. Single-basin solar still can be used for water desalination. Probably, they are considered the best solution for water production in remote, arid to semi-arid, small communities, where fresh water is unavailable. However, the amount of distilled water produced per unit area is somewhat low which makes the singlebasin solar still unacceptable in some instances. The purpose of this work is to study the effect of using different dye solutions in a solar still, and thus enhance the productivity of water. Experimental results show that the productivity of distilled water was enhanced for some materials. Using Methyline Blue solution increased the daily water productivity by 18%. While using Methyle Orange solution increased by 28 %. Also the better efficiency of 74.3 % has taken when using Methyle Orange solution compared with efficiency of 62.53 % when Methylene Blue solution was used while the better efficiency is 58.89 % when only water used in still. Therefore it is concluded the productivity of water still per unit area is increased when using dye solutions as Methylene Blue solution and Methyle Orange solution.